Diversification, Introgression, and Rampant Cytonuclear Discordance in Rocky Mountains Chipmunks (Sciuridae: Tamias). (7th January 2021) - Sarver, Brice A J; Herrera, Nathanael D; Sneddon, David; Hunter, Samuel S; Settles, Matthew L; Kronenberg, Zev; Demboski, John R; Good, Jeffrey M; Sullivan, Jack
Abstract: Evidence from natural systems suggests that hybridization between animal species is more common than traditionally thought, but the overall contribution of introgression to standing genetic variation within species remains unclear for most animal systems. Here, we use targeted exon capture to sequence thousands of nuclear loci and complete mitochondrial genomes from closely related chipmunk species in the Tamias quadrivittatus group that are distributed across the Great Basin and the central and southern Rocky Mountains of North America. This recent radiation includes six overlapping, ecologically distinct species ( Tamias canipes, Tamias cinereicollis, Tamias dorsalis, T. quadrivittatus, Tamias rufus, and Tamias umbrinus ) that show evidence for widespread introgression across species boundaries. Such evidence has historically been derived from a handful of markers, typically focused on mitochondrial loci, to describe patterns of introgression; consequently, the extent of introgression of nuclear genes is less well characterized. We conducted a series of phylogenomic and species-tree analyses to resolve the phylogeny of six species in this group. In addition, we performed several population-genomic analyses to characterize nuclear genomes and infer coancestry among individuals. Furthermore, we used emerging quartets-based approaches to simultaneously infer the species tree (SVDquartets) and identify introgression (HyDe). We found that, in spite of rampant introgression of mitochondrial genomes between some species pairs (and sometimes involving up to three species), there appears to be little to no evidence for nuclear introgression. These findings mirror other genomic results where complete mitochondrial capture has occurred between chipmunk species in the absence of appreciable nuclear gene flow. The underlying causes of recurrent massive cytonuclear discordance remain unresolved in this group but mitochondrial DNA appears highly misleading of population histories as a whole. Collectively, it appears that chipmunk species boundaries are largely impermeable to nuclear gene flow and that hybridization, while pervasive with respect to mtDNA, has likely played a relatively minor role in the evolutionary history of this group. [Cytonuclear discordance; hyridization; introgression, phylogenomics; SVDquartets; Tamias .]